Social Support and a Growth Mindset: An Autoethnography of a Vietnamese Doctoral Student in Canada - Le, Thu Thi Kim (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2026)
This autoethnography study examines how social support and a growth mindset shape the adaptation and resilience of a Vietnamese doctoral student in Canada. Grounded in social capital theory and growth mindset theory, it explores how bonding, bridging, and maintained forms of social capital interact with agency to mitigate academic, financial, and emotional stress. Drawing on personal narratives, reflective journals, and memory work, three interconnected themes emerged: (1) family emotional support and cultural continuity, which provided psychological grounding and a sense of belonging; (2) academic networking and institutional support, which fostered esteem, professional identity, and scholarly collaboration; and (3) professional growth through a growth mindset, which transformed challenges into opportunities for development. Findings reveal that growth mindset is not merely an individual trait but also a relational process enacted through networks of emotional, informational, social companionship, and instrumental support. It operates as a mediating force that activates social capital and situates agency within supportive contexts. This research contributes to international doctoral education by offering a nuanced understanding of social capital, social support, and mindset as interdependent dimensions of adaptation. It emphasizes inclusive, relational environments that empower international students to thrive academically and personally.